The power of knowledge for human evolution / Nik Muhamad Amir Nik Mustaffa and Nur Jazlina Ramli - Nik Mustaffa, Nik Muhamad Amir; Ramli, Nur Jazlina (Faculty of Information Management, 2015)
Knowledge, as everyone knows, is an important thing that everybody must attain in order to succeed in their life. Some of the people nowadays might think that knowledge is not that important as there is anything else in their mind that is more important in order to expand our life to be better. It is something that starts from something unknown call raw materials that turns into information which everyone knows what it is, and later become knowledge which is something that everybody can make use of it to get something new. So, this is what everybody should have known from earlier that knowledge plays a big role in deriving a better evolution phase for human life. Without knowledge, human might not evolved or go through an evolution phase that lead to a modernized world as we can see today. The aim is to ensure that every reader of this paper to understand what is knowledge as the power for human evolution and how does knowledge as the power could affect the evolution phase of human as well as their better future plan.